2003
DOI: 10.1128/mcb.23.23.8614-8625.2003
|View full text |Cite
|
Sign up to set email alerts
|

Ets2-Dependent Stromal Regulation of Mouse Mammary Tumors

Abstract: The Ets2 transcription factor is regulated by mitogen-activated protein (MAP) kinase phosphorylation of a single threonine residue. We generated by gene targeting a single codon mutation in Ets2 substituting Ala for the critical Thr-72 phosphorylation site (Ets2 A72 Most cancers are epithelial in origin. However, a significant and sometimes predominate portion of breast, colon, stomach, and pancreas tumors are host fibroblasts, endothelial cells, inflammatory cells, smooth muscle cells, adipocytes, and extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 61 publications
4
75
0
Order By: Relevance
“…Similarly, inhibition of MMP9 production in tumour-associated macrophages by a hypomorphic Ets-2 mutation also inhibited tumour development in the PyMT mouse model of breast cancer (Man et al, 2003). These data confirms the involvement of macrophages in tumour development in mouse models.…”
Section: Note Added In Proofsupporting
confidence: 69%
“…Similarly, inhibition of MMP9 production in tumour-associated macrophages by a hypomorphic Ets-2 mutation also inhibited tumour development in the PyMT mouse model of breast cancer (Man et al, 2003). These data confirms the involvement of macrophages in tumour development in mouse models.…”
Section: Note Added In Proofsupporting
confidence: 69%
“…Targeted deletion of the Ets2 DNA-binding domain (Ets2 db1 ) or mutation of the unique, activating MAPK phosphorylation site (Ets2 A72 ) revealed that Ets2 supports both autochthonous and transplanted mammary tumors (Man et al, 2003). The Ets2-dependent host effect on transplanted tumors showed that at least part of the function of Ets2 was mediated through the stroma (Man et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted deletion of the Ets2 DNA-binding domain (Ets2 db1 ) or mutation of the unique, activating MAPK phosphorylation site (Ets2 A72 ) revealed that Ets2 supports both autochthonous and transplanted mammary tumors (Man et al, 2003). The Ets2-dependent host effect on transplanted tumors showed that at least part of the function of Ets2 was mediated through the stroma (Man et al, 2003). However, a possible epithelial role for Ets2 is suggested by reversal of the transformed phenotype of BT20 breast tumor cells by a dominantnegative Ets2 construct (Sapi et al, 1998), but such constructs also broadly inhibit Ets family transcription factor function (Hever et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-associated macrophages have been reported to express MMP-9 in a number of mouse models of cancer, including squamous carcinomas of the skin (18) and cervix (19) and carcinomas of the breast (20,21). When stained with anti-CD68 (Fig.…”
mentioning
confidence: 99%